Recombinant Human Thymosin Beta-4 Protects against Mouse Coronavirus Infection. (21st April 2021) - Yu, Rui; Mao, Yunyun; Li, Kai; Zhai, Yanfang; Zhang, Yue; Liu, Shuling; Gao, Yuemei; Chen, Zhengshan; Liu, Yanhong; Fang, Ting; Zhao, Mengsu; Li, Ruihua; et al.
Abstract : Coronaviruses (CoVs) are enveloped and harbor an unusually large (30–32 kb) positive-strand linear RNA genome. Highly pathogenic coronaviruses cause severe acute respiratory syndrome (SARS) (SARS-CoV and SARS-CoV-2) and Middle East respiratory syndrome (MERS) (MERS-CoV) in humans. The coronavirus mouse hepatitis virus (MHV) infects mice and serves as an ideal model of viral pathogenesis, mainly because experiments can be conducted using animal-biosafety level-2 (A-BSL2) containment. Human thymosin beta-4 (T β 4), a 43-residue peptide with an acetylated N-terminus, is widely expressed in human tissues. T β 4 regulates actin polymerization and functions as an anti-inflammatory molecule and an antioxidant as well as a promoter of wound healing and angiogenesis. These activities led us to test whether T β 4 serves to treat coronavirus infections of humans. To test this possibility, here, we established a BALB/c mouse model of coronavirus infection using mouse CoV MHV-A59 to evaluate the potential protective effect of recombinant human T β 4 (rhT β 4). Such a system can be employed under A-BSL2 containment instead of A-BSL3 that is required to study coronaviruses infectious for humans. We found that rhT β 4 significantly increased the survival rate of mice infected with MHV-A59 through inhibiting virus replication, balancing the host's immune response, alleviating pathological damage, and promoting repair of the liver. These results will serve as the basis for further application of rhT β 4 to the treatment of human CoV diseases such as COVID-19.